1999
DOI: 10.1139/v99-095
|View full text |Cite
|
Sign up to set email alerts
|

The phosphoryl and the carbonyl group as hydrogen bond acceptors

Abstract: Formation constants for the hydrogen-bonded complexes between phenol (donor) and selected carbonyl or phosphoryl compounds (acceptors) were determined from IR Δν shifts. The P=O group is about two orders of magnitude stronger as an acceptor than the C=O group, but no evidence for the enolization of a β-diphosphoryl system was found. The IR absorption band of the phosphoryl group (νP=O) showed weak response to the involvement in the hydrogen bonding, and the shifts of the donor molecule (νOH) provide a better m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The mixed‐valence dimanganese complex [(bpy) 2 Mn(μ 2 ‐O) 2 Mn(bpy) 2 ](ClO 4 ) 3 50 and the phosphate ligands NBu 4 [O 2 P(O t Bu) 2 ]51 and NBu 4 [O 2 P(pin)]68 were synthesized as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The mixed‐valence dimanganese complex [(bpy) 2 Mn(μ 2 ‐O) 2 Mn(bpy) 2 ](ClO 4 ) 3 50 and the phosphate ligands NBu 4 [O 2 P(O t Bu) 2 ]51 and NBu 4 [O 2 P(pin)]68 were synthesized as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Modro et al [38] have evidenced the formation of strong hydrogen-bonded complexes between phenol (donor) and phosphoryl compounds (acceptor). They found that the hydrogen bonding properties of the P@O group was approximately 100-fold more effective than carbonyl group in a similar molecular structure.…”
Section: Catalytic Effect Of the Phosphonate Functionmentioning
confidence: 99%
“…1 For simple carbonyl compounds the K assoc values were determined from the ν OH for the donor. The obtained values are in the range 7-12, and agree well with the literature data.…”
Section: Phosphorus Sulfur and Silicon And The Related Elementsmentioning
confidence: 99%